HUMAN RESOURCES AND MARKETING MIX IN OIL&GAS INDUSTRY - MIHALCEA, Alina Daniela (Annales Universitatis Apulensis Series Oeconomica, 2015)
In the actual global knowledge society, all organizations have human resources systems implemented. What will make differences between organizations? people and their capacity to adapt, to sell themselves, to sell ideas, to sell projects. The paper intends to present connection between human resources and marketing in a dynamic and complex field, in oil& gas industry. Why and what means the “4P” and how your employees can apply in their organizational life can make a difference between organizations in a knowledge society.